The Contribution of Plant Dioxygenases to Hypoxia Signaling - Iacopino, Sergio; Licausi, Francesco (Frontiers in Plant Science, 2020)
Dioxygenases catalyze the incorporation of one or two oxygen atoms into target organic substrates. Besides their metabolic role, these enzymes are involved in plant signaling pathways as this reaction is in several instances required for hormone metabolism, to control proteostasis and affects chromatin accessibility. For these reasons, alteration of dioxygenase expression or function can affect plant growth, development and adaptation to abiotic and biotic stresses. Moreover, the requirement of co-substrates and co-factors, such as oxygen, 2-oxoglutarate and iron (Fe2+), invests dioxygenases with a potential role as cellular sensors for these molecules. For example, inhibition of cysteine deoxygenation under hypoxia elicits adaptive responses to cope with oxygen shortage. However, biochemical and molecular evidence regarding the role of other dioxygenases under low oxygen stresses is still limited, and thus further investigation is needed to identify additional sensing roles for oxygen or other co-substrates and co-factors. Here, we summarize the main signaling roles of dioxygenases in plants and discuss how they control plant growth, development and metabolism, with a focus on the adaptive responses to low oxygen conditions.